Zr‐Containing Hybrid Organic–Inorganic Mesoporous Materials: Hydrophobic Acid Catalysts for Biodiesel Production. Issue 4 (21st January 2013) - Sánchez‐Vázquez, Rebeca; Pirez, Cyril; Iglesias, Jose; Wilson, Karen; Lee, Adam F.; Melero, Juan A.
Abstract Zirconium‐containing periodic mesoporous organosilicas (Zr‐PMOs) with varying framework organic content have been synthesized through a direct synthesis method. These materials display the excellent textural properties of the analogous inorganic solid acid Zr‐SBA‐15 material. However, the substitution of silica by organosilicon species provides a strong hydrophobic character. This substitution leads to meaningful differences in the environment surrounding the zirconium metal sites, leading the modification of the catalytic properties of these materials. Although lower metal incorporation is accomplished in the final materials, leading to a lower population of metal sites, hydrophobisation leads to an impressive beneficial effect on the intrinsic catalytic activity of the zirconium sites in biodiesel production by esterification/transesterification of free fatty acid ‐containing feedstock. Moreover, the catalytic activity of the highly hybridised materials is hardly affected in presence of large amounts of water, confirming their very good water‐tolerance. This makes Zr‐PMO materials interesting catalysts for biodiesel production from highly acidic water‐containing feedstock.